2017
DOI: 10.1186/s12884-017-1259-y
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing’s actually happened to me.”: the experiences of fathers who found childbirth traumatic

Abstract: BackgroundGiven the limited research into men’s experiences of being present at childbirth this study explored the experiences of fathers who found childbirth traumatic. The aim of the research was to investigate how men coped with these experiences; the impact on their lives; and their views on what may have helped to reduce distress.MethodsParticipants were recruited via websites relating to birth trauma and parenthood. A consent and screening questionnaire was used to ensure that participants met the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 33 publications
10
118
0
4
Order By: Relevance
“…The impact of traumatic birth had serious implications for some of the participants in the current study, with mental health issues such as depression, anxiety, postnatal stress, obsessive-compulsive disorder (OCD) and PTSD symptoms being described. Similar mental health difficulties and relationship problems for fathers following their traumatic experiences have been reported elsewhere [6][7][8][9]. Fathers also talked about how the relationship with their infant had been affected.…”
Section: Findings and Interpretationmentioning
confidence: 52%
See 2 more Smart Citations
“…The impact of traumatic birth had serious implications for some of the participants in the current study, with mental health issues such as depression, anxiety, postnatal stress, obsessive-compulsive disorder (OCD) and PTSD symptoms being described. Similar mental health difficulties and relationship problems for fathers following their traumatic experiences have been reported elsewhere [6][7][8][9]. Fathers also talked about how the relationship with their infant had been affected.…”
Section: Findings and Interpretationmentioning
confidence: 52%
“…Vogel et al [19] reported similar findings. Previous studies have shown how fathers' coping strategies were influenced by their beliefs about masculinity [8] and how men experience psychological distress when they fail to live up to internalised beliefs of masculinity [27]. Fathers may struggle with overcoming trauma and seeking help.…”
Section: Findings and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited research has addressed the impact of traumatic birth on fathers. Etheridge and Slade (2017) in a qualitative study, examined the impact of their partners' birth trauma in 11 fathers. They found that fathers experienced birth as a rollercoaster of emotions, characterised by 'isolation and abandonment'.…”
mentioning
confidence: 99%
“…A recent qualitative study of fathers who experienced a traumatic birth and met some PTSD criteria suggested that the subjective nature of the perception of the birth was crucial and this may have implications for the development of PTSD symptomology (Etheridge & Slade, 2017). Recent work has shown that it is feasible and acceptable to fathers to administer multiple research questionnaires when investigating this area (Bagge, Westgate, Few, Clarke, & Adlam, 2017).…”
Section: Future Researchmentioning
confidence: 99%